2011
DOI: 10.4049/jimmunol.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Runx1/Cbfβ2 Complexes Are Required for Lymphoid Tissue Inducer Cell Differentiation at Two Developmental Stages

Abstract: Hematopoietic lymphoid tissue inducer (LTi) cells are essential for the development of secondary lymphoid tissues including lymph nodes and Peyer’s patches. Two transcription factors, the helix-loop-helix inhibitor Id2 and the retinoic acid-related orphan receptor γt (Rorγt), have been shown to be crucial for LTi cell development. However, it remains unclear how the specification of multipotent hematopoietic progenitor cells toward the LTi lineage is programmed. In this study, we report impaired lymphoid tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 43 publications
3
70
1
Order By: Relevance
“…In addition to these granulocytes, numbers of monocytes (Gr-1 low Siglec-F Ϫ ), NK cells (NK1.1 ϩ CD3 Ϫ ), total T cells (CD3 ϩ ), B cells (B220 ϩ ), and dendritic cells (CD11c ϩ ) were not significantly different in Runx1 P1N/P1N mice compared with WT mice in either the BM or spleen (Figure 2A-B). As we reported previously, 40 NKT cells (NK1.1 ϩ CD3 ϩ ) were reduced in both the BM and spleen (Figure 2A-B). These data indicate that, among granulocyte populations, basophils are uniquely deficient in Runx1 P1N/P1N mice.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In addition to these granulocytes, numbers of monocytes (Gr-1 low Siglec-F Ϫ ), NK cells (NK1.1 ϩ CD3 Ϫ ), total T cells (CD3 ϩ ), B cells (B220 ϩ ), and dendritic cells (CD11c ϩ ) were not significantly different in Runx1 P1N/P1N mice compared with WT mice in either the BM or spleen (Figure 2A-B). As we reported previously, 40 NKT cells (NK1.1 ϩ CD3 ϩ ) were reduced in both the BM and spleen (Figure 2A-B). These data indicate that, among granulocyte populations, basophils are uniquely deficient in Runx1 P1N/P1N mice.…”
supporting
confidence: 86%
“…34 We had demonstrated previously a requirement for P1-Runx1 in lymphoid tissue inducer cell differentiation, 40 and found that Runx1 P1N/P1N mice have severe reductions in NKT cells, mild T-cell deficits, and an increase in Lin Ϫ c-Kit ϩ Sca-1 ϩ HSCs. 40 However, there have been no previous reports describing the myeloid cell compartment in these mice. When we analyzed myeloid cells in Runx1 P1N/P1N mice, we found that they have a severe reduction in basophils.…”
mentioning
confidence: 94%
“…It has been demonstrated that Notch signaling helps to maximize the efficiency of LTi cell differentiation [41]. Likewise, LTi cell differentiation needs to some transcriptions factors such as Runx1 and Tox [68,69]. Furthermore, aryl hydrocarbon receptor (AhR) signals are required for the maintenance and expansion of postnatal emerging of ILC3 subset [47].…”
Section: Ilc Developmentmentioning
confidence: 99%
“…(10,19,21) In brief, with the splice signal for Cbfb1 located inside of exon 5, the GTG was mutated to CTC, and with the splice signal for Cbfb2 at the 3' terminus of exon 5, GTTAG was mutated to AATTC. Cbfb fl/fl/Cre mice were generated by using Cbfb fl/fl mice and Dermo1 Cre knock-in mice, in which Cre is expressed in mesenchymal cells giving rise to both chondrocyte and osteoblast lineages.…”
Section: Micementioning
confidence: 99%
“…(17,18) Cbfb1 and Cbfb2 are formed by alternative splicing using donor splice sites located inside exon 5 and at the 3' terminus of exon 5, respectively, and an acceptor splice site located at the 5' terminus of exon 6. (18) Although Cbfb2 is required for the differentiation of lymphoid tissue inducer cells and the development of mucosa-associated lymphoid tissue, (19,20) the functions of the two isoforms in skeletal development are completely unknown. In this study, we examined the skeletal development of mice lacking the Cbfb1 isoform (Cbfb1 -/-) and mice lacking the Cbfb2 isoform (Cbfb2 -/-).…”
mentioning
confidence: 99%